The Effect of Knowledge Levels of Breastfeeding Mothers About the Disease on Their Levels of Anxiety During the COVID-19 Pandemic Process - Selda Ayşe Tekiner; Nisa Eda Çullas Ilarslan; Fatih Günay; Gülsen Ayşe Ceyhun Peker (Frontiers Media S.A., 2022)
Background:The health impact of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) spans across all age groups including mothers and their newly born infants; and breastfeeding women during this pandemic deserves special attention due to its short and long-term health implications. When planning the current study, our hypothesis was that the anxiety of transmitting the COVID-19 disease to the baby through breastfeeding would increase among breastfeeding women and it would predominantly be state anxiety. The current study aims to investigate the relationship between the knowledge levels of breastfeeding mothers about COVID-19 and their anxiety levels.Materials and MethodsThis is a cross-sectional study and we aimed to reach all mothers with babies between 0 and 24 months of age who applied to the Healthy Child Care Policlinic of Ankara University Faculty of Medicine Hospital between July 1 and August 31, 2020 Questionnaires measuring the level of knowledge about COVID-19 disease and breast milk and questionnaires measuring anxiety levels were administered to mothers. The state-trait anxiety levels and knowledge levels of breastfeeding mothers about COVID-19 disease, as well as their knowledge levels about breast milk and sociodemographic characteristics were compared.ResultsA total of 145 breastfeeding mothers were included in the study. The trait anxiety was found to be either absent or mild in 89 (61.4%), moderate in 28 (19.3%), and advanced in 28 (19.3%) mothers. The state anxiety level, however, was found to be either absent or mild in 51 (35.2%), moderate in 42 (29%), and advanced in 52 (35.9%) mothers. When mothers' trait and state anxiety levels and their knowledge levels about breast milk, their knowledge levels about COVID-19 disease and their sociodemographic characteristics were compared, it was determined that mothers with 0-6 months old infants had lower state anxiety levels compared to mothers with older infants. However, the anxiety levels of mothers whose children were >12 months old were mostly moderate (p < 0.05). There was no statistically significant difference in terms of other variables (p < 0.05). A positive correlation was found between the child age and state anxiety level (p = 0.027).ConclusionModerate and advanced level of state anxiety was found to be higher than level of trait anxiety parallel to our hypothesis. Among breastfeeding mothers, those with the lowest state anxiety scores were those who had babies between 0 and 6 months. It is important to support breastfeeding mothers in promoting breastfeeding, especially after 6 months of birth. Policymakers, obstetricians and especially the family physicians should be aware that adverse life events may put a higher burden on the emotional wellbeing of breastfeeding women especially after 6 months of birth of the babies. So, breastfeeding promotion, protection and support strategies should be reconsidered specially after 6 months.